Speech and respect. Richard Abel - A. Kenyon (Law Text Culture, 1997)
Australia has seen wide ranging debates about the High Court's implied rights jurisprudence during the 1990s. The Constitution has been found to limit the legal control of political discussion. The doctrine survives, although apparently with less energy, after changes in the Court's composition during 1995 and decisions such as McGinty v Western Australia. Most commentators suggest the Court has stepped back from its previous activism. Two forthcoming decisions may even remove political discussion as an issue of constitutional doctrine, at least in relation to the law of civil defamation. Following the High Court cases, however, political discussion exists as a central concept for Australian jurisprudential, constitutional and media related legal theory about the control of expression.